Identificación y localización de fallas en sistemas de distribución, utilizando medidores de calidad del servicio de energía eléctrica - Gómez, Víctor A.; Peña, Robín A.; Hernández, César (Revista Científica, 2012)
This paper presents a new methodology for identifying and locating faults in distribution systems of electric power, through the implementation of electronic meters that record the continuity of electric service. The implementation of the meters, to provide detection permanent or transient faultin non-homogeneous networks and providing information of weaknesses in the power system and then to take corrective action with respect to the duration and frequency of breaks in the circuits local distribution systems. By means of this mechanism regulation of the systems from the generation, marketing, distribution and operation of electricity. This raises a solution to mitigate the discontinuity of service and significant costs to produce electricity sector agents and mainly to electricity users.